'I became a teacher that respects the kids' voices': challenges and facilitators pre-service teachers faced in learning an activist approach. Issue 4 (3rd May 2020) - Luguetti, Carla; Oliver, Kimberly L.
ABSTRACT: Several studies demonstrate the benefits of educating for social justice in physical education teacher education programs [O'Sullivan, M. (2018). PETE Academics as public intellectuals and activists in a global teacher education context. Physical Education and Sport Pedagogy, 23 (5), 536–543], which supports that pre-service teachers (PSTs) have the capacity to be active agents of change. In working with social justice, PSTs engage in what can be a very personal struggle with their own stereotypes and assumptions about the people they are working with [Oliver, K. L., Oesterreich, H. A., Aranda, R., Archeleta, J., Blazera, C., Crux, K.,  … Robinson, R. (2015). 'The sweetness of struggle': Innovation in physical education teacher education through student-centered inquiry as curriculum in a physical education methods course. Physical Education and Sport Pedagogy, 20 (1), 97–115]. Although the challenges that PSTs faced to learn an activist approach to teaching are described in the literature, there is little research that aims to understand how these challenges progress across time. The aim of this study is to explore the challenges pre-service teachers faced when learning to use an activist approach across time. Participatory action research framed this 3-semester study (18 months). Participants included 10 pre-service-teachers, 90 youth, and two researchers. Data collected included: (a) collaborative PSTs group meetings; (b) PSTs reflective diaries after each teaching episode; (c) lead researcher observations collected as field notes; (d) PSTs generated artifacts; and (e) PSTs interviews and focus groups. Data analysis involved inductive and constant comparison. Results conveyed: (a) the PSTs' assumptions about what student-centered pedagogy meant and the challenges of overcoming their misconceptions about teaching and learning; and (b) the PST's struggles in coming to understand themselves as activist teachers, with dispositions as advocates of social justice. Future studies should continue to explore the challenges and facilitators PSTs face when learning an activist approach aimed at empowering both students and teachers to develop a critically conscious understanding of their relationships with the world through their effort to name and change the world together.